Analisis Pengetahuan, Kepatuhan, dan Outcome Klinis Pasien Hipertensi di Puskesmas Jetis Yogyakarta - Husna, Nadia; Sugiyono, Sugiyono; Yunilistianingsih, Yunilistianingsih (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Hypertension has been an increasing global epidemic problem over years and considered as one of the deadly disease with a high cardiovascular complication risk. Knowledge and adherence play an important role in patient's clinical impact, which determined the level of medication’s adherence. Thus, adherence level determines the achievement of clinical outcome. The optimum clinical optimum will be achieved if the adherence level is at good level. The method in this study was using observational analytics with a cross sectional approach. The sampling method was consecutive sampling. The subjects were the adult hypertensive patients at Puskesmas Jetis Kota from August until October 2020. Univariate analysis was conducted in patient’s and medication characteristics. Kendal Tau test was used to analyze the relationship between adherence and clinical outcome. 81 hypertensive patients were included in this study. The highest prevalence of patient’s characteristics were shown on the women’s group: 45-59 years old, senior high school education background, and no occupation. Amlodipine was the highest medication used as a single therapy. It was found that there is no relationship between knowledge and adherence level. In addition to that, there was no relationship between adherence level and clinical outcome measured by systole and diastole.